IMPLEMENTATION OF A "CONTROL DIARY" FOR SELF-CONTROL BY PATIENTS WITH BRONCHIAL ASTHMA AND ASSESSMENT OF ITS EFFECTIVENESS - Razikova Ilmira Sadullaevna; Alikulova Dildora Yakhshibaevna; Abdullaeva Barno Khikmatullaevna (Scholar Express Journals, 2023)
Assessment of the effectiveness of the nursing approach in bronchial asthma by training nurses to develop their skills and medical level according to the nursing approach algorithm for patients with bronchial asthma and by implementing a control diary for self - control of patients.
Keywords: Asthma; implementing; effectiveness